Relationship among personal characteristics, job satisfaction and burnout levels of faculty members in Colegio San Agustin, Makati - Guerrero, Ma. Angelica Bejar (Animo Repository, 1991)
This study investigates the relationships among personal characteristics, job satisfaction and burnout levels of faculty members in Colegio San Agustin, Makati during school year 1990-1991. Specifically, the study seeks: 1.0 To determine the demographic profile of the faculty members of Colegio San Agustin in terms of: 1.1 Sex1.2 Age1.3 Civil status 1.4 Educational Qualifications 1.5 Years of Teaching. 2.0 To determine the burnout level of the faculty members of Colegio San Agustin in terms of the following subscales of the burnout syndrome: 2.1 Emotional Exhaustion 2.2 Depersonalization 2.3 Reduced Personal Accomplishment 3.0 To determine the job satisfaction level of the faculty members of Colegio San Agustin.4.0 To determine the relationship between the respondents personal characteristics and burnout level. 5.0 To determine the relationship between the respondents' personal characteristics and job satisfaction level. 6.0 To determine the relationship between the respondents' burnout and job satisfaction levels. The descriptive research design using the survey method with correlational treatment was utilized in this study. One hundred eighty eight (188) teacher respondents from the pre school, elementary and secondary levels of Colegio San Agustin, Makati during schoolyear 1990-1991, comprised the subjects of this research. The instruments used were Maslach's Burnout Inventory (MBI) which measured three subscales of the burnout syndrome, namely: Emotional Exhaustion, Depersonalization and Personal Accomplishment and Hoppock's Job Satisfaction Blank (JSB) which measured the job satisfaction level. A separate teacher background information section was also included to determine background information of sex, age, civil status, educational qualification and years of teaching experience. Statistical treatment applied were computations of means and percentages, as well as Pearson r correlational analysis set at .01 and .05 level of significance, making use of the computer services of the Statistical Assistance for Research (STAR) center. The following are the significant findings of the study: 1. Faculty members of Colegio San Agustin in Makati generally exhibit low to moderate levels of burnout. Specifically, moderate scores were obtained in the frequency of emotional exhaustion, intensity of depersonalization and frequency and intensity of reduced personal accomplishment. On the other hand, low scores were obtained in the frequency of depersonalization and intensity of emotional exhaustion. 2. The job satisfaction level of the teacher respondents is fairly good, 5.36 in the scale of 7.3. There exists a significant relationship between the variable of educational qualification and the intensity of emotional exhaustion (r = -.168 p = .05).4. There exists no significant relationship between the personal characteristics and the subscales of burnout. In other words, the personal variables of sex, age, civil status, and years of teaching experience are not significant predictors of teacher burnout. 5. There exists no significant relationship between the personal characteristics and the job satisfaction level. In other words, personal variables of sex, age, civil status, educational qualification and years of teaching experience are not significant predictors of job satisfaction. 6. There exists significant relationship between the subscales of burnout and job satisfaction level. Specifically, the relationships are significant between the: 6.1 Frequency and intensity of Emotional Exhaustion and Job Satisfaction level (r = -.489 & - .456 p .01).